ORDER PROCESS FLOW OF MASS CUSTOMIZATION BASED ON SIMILARITY EVALUATION - Xuanguo, XU (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
The main result presented in this paper is the order process flow of mass customization based on similarity evaluation. An order process flow of mass customization is put forward with a view to meet customers’ specific needs as well as to reduce difficulties in subsequent production. As the basis of this order process flow, we suppose that all the orders in the accepted order pool are profitable confirmed by the market. A similarity evaluation method is put forward which includes the following steps: determine whether an order is acceptable or not; put the profitable order into the accepted pool; for those not profitable, negotiate with customer to determine which pool it belongs to; order similarity analysis with system clustering method; arrange for batch production for those have much similarities; arrange for completely customized production for those specific orders; arrange order insertion for those have little similarity but can be inserted to the scheduled plan. At the end of this paper, an example case study of one China Air Conditioning Company is presented to illustrate the application of the process flow and the similarity evaluation method.